DOCTORAL PROGRAMS IN ACCOUNTING. - Carson, A. B.; Kaulback, Frank S.; Morrison, Lloyd F.; Moss, Morton F.; Schiff, Michael; Terrill, William A. (The Accounting Review, 1958)
Twenty nine universities in the U.S. offer doctoral programs that will "fit the needs of a student whose primary interest is to prepare for a career of either the teaching of accounting or research in accounting." A survey of these programs was undertaken by the Task Committee on Standards of Graduate Instruction, formed early in 1957 to succeed the Task Committee on Standards of Accounting Instruction. The article summarizes the information the committee gathered during its first year of operation. At three universities the students whose primary interest is accounting pursue their doctoral studies under the jurisdiction of the economics department. In two cases the program is jointly conducted in economics and business administration. In all other instances, the Department or School (College, Division) of Business Administration offers and administers the degree program, subject, in most instances, to general, university-wide requirements. The Committee was interested in institutional practices with respect to any student who wished to major in accounting in his doctoral program without having had the minimum course requirements for a master's degree in accounting.